PRADAEC Learning Model in Determining the Success of al-Qur’an Hadith Cognitive Learning and as a Religious Moderation Among Students of Islamic Schools - Ely Mufidah; Ismail Ismail; Ibnu Hadjar; Ahmad Luqman Hakim (Faculty of Education and Teacher Training, Institut Agama Islam Negeri Pekalongan, 2022)
Al-Qur'an Hadith are sources of law for Muslims. It is crucial to apply teaching and learning models that are easy for teachers and students to understand and form religious moderation. This study explains how the PRADAEC learning model determines the success of cognitive learning of Islam students while also accommodating religious moderation. Based on the results of this library study, there are seven stages (syntax) in the PRADAEC learning model: Preview, Read, Ask, Discuss, Answer, Explain, and Correction. Second, the seven stages of the PRADAEC learning model are then implemented in three learning components, namely: 1) Introduction, including Preview, 2) core activities, namely Read, Ask, Discuss, Answer and Explain and 3) Closing, namely Correction. Third, the stages (syntax) of the learning process include Preview, Read, Ask, Discuss, Answer, Explain, and Correction. The conditions show that the PRADAEC model improves the cognitive learning of Al-Qur'an Hadith while also accommodating students' religious moderation. The enhancement of local school values such as honesty, mutual respect, and courtesy among students needs to concern the values, assumptions, understandings, beliefs, and expectations that are upheld and used by the school, which determines the behaviors in dealing with internal and external parties.